Thermodynamic analysis of glycerol dry reforming - Latifah Sakinah, Ismail (2013)
The growing demand for hydrogen energy requires renewable raw materials for its production. In particular, production of alternatives fuels such as biodiesel and ethanol has increased over the last few years culminating in increased glycerol output, a byproduct of transesterification. Due to the increased production of biodiesel, it is imperative to find alternative uses for glycerol such as for hydrogen production. Hydrogen is produced by using several processes such as steam reforming, autothermal reforming, aqueous-phase reforming and supercritical water reforming. Most of studies concern with hydrogen production via steam reforming process. To date, few works have been dedicated to produce hydrogen from glycerol dry reforming. Significantly, since glycerol has more carbon atoms than ethanol, it may be more likely to produce carbon nanofilaments (CNF) which is a potential marketable byproduct. This research reviews the several of synthesis gas produced in term of thermodynamic analysis such as methane, carbon, carbon dioxide, hydrogen and carbon monoxide. This research analysis by using glycerol as substrate with the aim of investigating the thermodynamics of glycerol dry reforming at atmospheric pressure and reforming temperature from 500 to 1000 K. Moles of each synthesis gases is shown with different of temperature and CGRs. On the basis of thermodynamic analysis with optimized operational condition, gaseous product distributions and coke formation behavior was obtained at different CGRs with different temperature. Based on this research, the synthesis gas have been produced which is hydrogen 1.5 moles, carbon monoxide 7.6 moles, carbon dioxide 5 moles, methane 1.5 moles and carbon 3 moles.